Weiterbildung, Arbeitszeit und Lohneinkommen - Friedhelm Pfeiffer; Joachim Brade (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
This paper analyzes the determinants, work-time and income effects of continuous vocational training in West-Germany on the basis of a 70% sample of the German Microcensus 1991 - a representative 1% cross-section sampIe of all German households. Several hypotheses about the influence of qualification, demographic effects, unionization and technological progress are explicitly tested combining additional data sources, notably the Mannheim Innovation Panel, 1993. The econometric analysis refers to West-German, male employees with a professional experience between 0 and 30 years. We find the probability of further training to be positively related to the level of schooling as weIl as vocational qualification - though less significantly. Technical progress, unionization and the aging of the population excert a positive influence on the probability of individual further training. Further training leads to considerable income effects, which range from 0% to 12% depending on the type and duration of further training undertaken. They are greater for shorter further training activities. Employees participating in further training also work longer. The work-time effects amount up to 9% according to the type and duration of training undertaken. Therefore income and wage effects differ from each other. Surprisingly far employees with a university or a technical college degree income effects are much lower.
Keywords: 330